2021
DOI: 10.1097/iae.0000000000002917
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Detachment With Inferior Retinal Breaks

Abstract: Introduction: Rhegmatogenous retinal detachments with inferior retinal breaks are believed to have a higher risk of recurrent rhegmatogenous retinal detachment. This study compared anatomic and visual outcomes between primary pars plana vitrectomy (PPV) and combination PPV with scleral buckle (PPV/SB) for rhegmatogenous retinal detachments with inferior retinal breaks. Methods: This is an analysis of the Primary Retinal Detachment Outcomes study, a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Retinal detachments with inferior breaks jeopardize single surgery success rates due to the potential for incomplete tamponade and higher risk of PVR. [1][2][3][6][7][8] The recent PRO study (report number 9) comparing anatomical success in eyes of patients with primary RD and a single inferior break found a significant advantage for PPV/SB (with an encircling band) (87.4%) vs PPV alone (76.8%) at 1-year follow-up. 6 Other recent studies, with different tamponade agents and lower than average success rates, have reported comparable outcomes with PPV vs PPV/SB alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Retinal detachments with inferior breaks jeopardize single surgery success rates due to the potential for incomplete tamponade and higher risk of PVR. [1][2][3][6][7][8] The recent PRO study (report number 9) comparing anatomical success in eyes of patients with primary RD and a single inferior break found a significant advantage for PPV/SB (with an encircling band) (87.4%) vs PPV alone (76.8%) at 1-year follow-up. 6 Other recent studies, with different tamponade agents and lower than average success rates, have reported comparable outcomes with PPV vs PPV/SB alone.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][6][7][8] The recent PRO study (report number 9) comparing anatomical success in eyes of patients with primary RD and a single inferior break found a significant advantage for PPV/SB (with an encircling band) (87.4%) vs PPV alone (76.8%) at 1-year follow-up. 6 Other recent studies, with different tamponade agents and lower than average success rates, have reported comparable outcomes with PPV vs PPV/SB alone. [6][7][8]14,15 Perhaps, the main caveat inherent to any retinal detachment study is the presence of variables which cannot always be well-accounted for which significantly Figure 1 The location of the inferior-most break is marked externally using a scleral depressor marker under direct visualization (A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations